Behavior toward energy: An exploration of high school students’ perspective in Indonesia - Zulkarnaen Zulkarnaen; Nurul Fitriyah Sulaeman; Atin Nuryadin; Ippei Mineta (International Journal of Evaluation and Research in Education (IJERE), 2023)
Securing universal access to affordable electricity by 2030 is one of the sustainable development goals. Meanwhile, energy consumption efficiency has a vital role in determining the achievement of this goal. Therefore, exploring behavior toward energy is crucial. Energy behavior is often characterized as individual actions that influence energy consumption and understanding of its production. On the other hand, the perspective of the young Indonesian generation is interesting to explore as their country is well-known as a fossil energy producer. In this study, the participants were 475 junior high school students in the ninth grade from four public schools in Indonesia. The questionnaire has 39 items that explore students’ perspectives on their behavior toward energy. The result shows that students’ energy behavior is mainly at a moderate level with no significant difference by gender. Students with experience in informal energy education showed higher energy behavior. The result suggests the urgency of a better quality of energy education, both formal and informal, that supports reinforcement in energy behavior.